Schulkulturen in der gymnasialen Oberstufe Eine explorative Studie zu kulturellen Passungsverhältnissen und Schule-Milieu-Komplexen in der Sekundarstufe II - Lojewski, Johanna (Oberstufe gestalten, 2023)
Based on repeated empirical evidence that the structure and organization of the German education system systematically ensure unequal educational and life chances, this work takes a look at the upper secondary level ("gymnasiale Oberstufe") as the central awarding body for the "Abitur" (A-Level), which has gained in quantitative importance over the last 60 years and at the same time has been exposed to considerable structural and contentual transformations. These developments, as well as the accompanying institutional and social diversification of upper secondary schools, will be examined from the perspective of the works on education by Bourdieu and Passeron, especially the "Theory of Symbolic Violence" (1973). More recent theoretical perspectives and connections are also discussed, which differentiate and complement their rather global assumptions.